The role of Group insurance and the Housing Fund in achieving the Environmental dimension of Sustainable Performance Objective (11) : Applied Research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The role of group insurance and the housing fund in achieving the environmental dimension of sustainable performance, goal (11) / Applied research The research aims to identify the relationship between group insurance and the Iraqi Housing Fund in achieving the environmental dimension of sustainable performance, goal (11). The data and financial reports of the research sample for the period 2019-2022 were studied and analyzed to determine the extent of the application of sustainability (environmental) indicators by the Housing Fund and group insurance activity. Indicators of loans granted to build houses and residential complexes at the Housing Fund and group insurance activity were used through the group insurance contracts that were completed during the research period for the environmental dimension and the extent of their consistency with the international environmental goals (SDGs).